Distrofia muscular progresiva en niñas. Presentación de 3 casos. - Menéndez Alejo, Ibis; González, Santiago Luis; Mustelier Becquer, Reinaldo; Sardiñas Hernández, Norberto (Revista Cubana de Pediatría, 2023)
Estudio realizado en tres niñas.